Evaluation of Serum 3‐Bromotyrosine Concentrations in Dogs with Steroid‐Responsive Diarrhea and Food‐Responsive Diarrhea. (19th June 2017) - Sattasathuchana, P.; Allenspach, K.; Lopes, R.; Suchodolski, J.S.; Steiner, J.M.
Abstract : Background: The clinical usefulness of serum 3‐BrY concentrations for subclassifying dogs with food‐responsive diarrhea (FRD) and steroid‐responsive diarrhea (SRD) has not been studied. Hypothesis/Objectives: To compare serum 3‐BrY concentrations in dogs with FRD, dogs with SRD, and healthy control dogs. Animals: 38 dogs with FRD, 14 dogs with SRD, and 46 healthy dogs. Methods: Prospective study. Measurement of 3‐BrY concentration in serum samples was performed by gas chromatography/mass spectrometry. Results: There was no association of peripheral eosinophilia in dogs with FRD, SRD, and healthy control dogs ( P = 0.069). There was no significant correlation between peripheral eosinophil counts and serum 3‐BrY concentrations (ρ = −0.15, P = 0.13). Serum 3‐BrY concentrations in dogs with SRD (median [range] = 3.27, 0.9–26.23 μmol/L) were significantly higher than in dogs with FRD (median [range] = 0.99, 0.62–8.82 μmol/L; P = 0.007) or in healthy dogs (median [range] = 0.62, 0.62–1.79 μmol/L; P < 0.001). Also, serum 3‐BrY concentrations in dogs with FRD were significantly higher than in healthy dogs ( P = 0.025). There was no significant correlation between the canine chronic enteropathy clinical activity index and serum 3‐BrY concentrations (ρ = 0.17, P = 0.23). Conclusions and Clinical Importance: Measurement of serum 3‐BrY concentrations, but not the peripheral eosinophil count, is helpful for detecting dogs with SRD and FRD.